Characteristics and prognostic value of right ventricular (dys)function in patients with non‐ischaemic dilated cardiomyopathy assessed with cardiac magnetic resonance imaging. (9th February 2021) - Becker, Marthe A.J.; van der Lingen, Anne‐Lotte C.J.; Wubben, Marc; van de Ven, Peter M.; van Rossum, Albert C.; Cornel, Jan H.; Allaart, Cornelis P.; Germans, Tjeerd
Abstract: Aims: In non‐ischaemic dilated cardiomyopathy (DCM), concomitant right ventricular (RV) dysfunction is frequently observed. This study sought to determine the correlation of RV dysfunction with several cardiac magnetic resonance (CMR) imaging characteristics in patients with DCM, and the prognostic value of RV dysfunction on all‐cause mortality and ventricular arrhythmias (VA) was evaluated. Methods and results: Consecutive patients with DCM and left ventricular (LV) dysfunction (ejection fraction < 50%) on CMR were included retrospectively. Left atrial (LA), LV, and RV volumes and function were quantified. RV systolic dysfunction was defined as RVEF<45%. The presence and pattern of late gadolinium enhancement (LGE) on CMR were assessed visually. Septal midwall LGE was defined as midmyocardial stripe‐like or patchy hyperenhancement in the septal segments, and the extent was quantified using the full width at half maximum method. Primary endpoint was a composite of all‐cause mortality and VA, including resuscitated cardiac arrest, sustained VA, and appropriate implantable cardioverter defibrillator therapy. Secondary endpoints were time to all‐cause mortality alone and time to VA alone. A total of 216 DCM patients were included (42% female, age 58 ± 14 years). Mean RVEF was 46 ± 12%, and RV dysfunction was present in 38%. RVEF was moderately correlated with LA dilation (LA minimal volume ρ = −0.38, P  < 0.001) and strongly correlated with LA and LV dysfunction (LA emptying fraction r  = 0.58, P  < 0.001 and LVEF ρ = 0.52, P  < 0.001). Septal midwall LGE was more often observed in patients with RV dysfunction compared with patients with preserved RV function (respectively 40% vs. 26%, P  = 0.04). No correlation was found between RVEF and the extent of septal midwall LGE (ρ = −0.12, P  = 0.34). During a median follow‐up of 2.2 years [IQR 1.6–2.8], 30 patients experienced the primary endpoint. RV dysfunction was significantly associated with shorter time to the composite primary endpoint (HR 3.19 [95% CI 1.49–6.84], P  < 0.01) and to the secondary endpoint of VA alone (HR 6.48 [95% CI 1.83–22.98], P  < 0.01). There was a trend towards increased mortality when RV dysfunction was present (HR 2.54 [95% CI 0.99–6.57], P  = 0.05). Conclusions: Right ventricular dysfunction was predominantly observed in patients with DCM with advanced heart failure and pronounced myocardial remodelling, defined as increased LV and LA dilation and dysfunction and the presence of septal midwall LGE on CMR. During follow‐up, RV dysfunction was associated with shorter time to all‐cause mortality and ventricular arrhythmic events.